Correction to: Beta diversity as an indicator of priority areas for Myrtaceae assemblage conservation in Subtropical Araucaria Forest - Pereira Gomes, Juliano; Bet Stedille, Lilian Iara; de Freitas Milani, Jaçanan Eloisa; Montibeller-Silva, Karina; Mantovani, Adelar; Lopes da Costa Bortoluzzi, Roseli (Biodiversity and conservation, 2020)
In the original publication of the article, Table 1 was published with few errors and the Acknowledgement statement was inadvertently omitted. The corrected table and acknowledgement statement is provided in this Correction.